Estimando a retração recente no preço de minério de ferro - Macedo, Gustavo Rodrigues (2015)
This study presents an analysis about the sharp fall in the price of iron ore observed during the year of 2014, using econometric methods to assess the impact of the strong increase in the volumes supplied to the seaborne market combined with a slowdown in some steel-intensive sectors in China. The study briefly presents the industry and the recent developments of the iron ore seaborne market, and then uses regression models to estimate determinant factors for iron ore price. The results indicate that a significant part of the price decline observed in 2014 cannot be explained by usual factors, suggesting that the atypical conditions observed during the year determined the market equilibrium.